Exploring L2 speech fluency of advanced learners from the perspective of linguistic self-confidence and communication confidence - Szyszka, Magdalena; Lintunen, Pekka; Pawlak, Mirosław (SAGE Publications, 2026)
This study explores the relationship between two facets of confidence in second language (L2) learning: linguistic self-confidence (LSC) and L2 communication confidence (L2 CC), and how they interplay with L2 speech fluency. The data were collected from 102 advanced L2 learners who performed a monologue task to capture their L2 speech fluency, measured in terms of breakdown fluency markers (mean length of silent pauses, frequency of filled and silent pauses), speed of speech (articulation rate), and composite indices (speech rate, phonation–time ratio, and mean length of run). The levels of L2 CC were established with the scale developed by Mystkowska-Wiertelak and Pawlak, while LSC levels were reported using a questionnaire designed for the purposes of the study. The results showed that LSC and L2 CC, while related, are distinct constructs. Regression analyses indicated that LSC accounted for 6% of the variance in speech rate and mean length of run, while L2 CC and LSC jointly predicted variation in frequency of filled pauses. Comparisons between groups with low and high levels of LSC revealed significant differences in temporal and breakdown L2 fluency indices; however, most of them lost statistical significance after applying corrections. The low and high L2 CC groups differed significantly in articulation rate. The outcomes of the study can serve as a basis for several implications for teaching and evaluating L2 speech.